Pemberdayaan Masyarakat Berdampak Bencana Banjir Bandang dalam Mengelolah Air Bersih Untuk Memenuhi Kebutuhan Air bersih Paska Bencana Banjir Bandang yang Melanda Aceh Tamiang - Dafid Ginting; Yuris Danilwan; Lilis Lilis; Aja Avriana Said; Yuna Sutria; Taruna Taruna; Dina Rispianti; Suratni Suratni; Fadiyah Hani Sabilah; Syarifur Ridho; Eka Fransiska; Irma Handayani; Fahmi Rinaldi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
One of the biggest problems after a flash flood and landslide disaster is the provision of clean water. Access to clean water is very important, as it greatly helps the disaster-affected community, especially in their future lives after the flood and landslide disaster in Aceh Tamiang. Community Service was carried out by the Lecturer Team of the Indonesian Maritime Adiguna Polytechnic Medan, who came directly to the Tamiang sub-district affected by the flash flood disaster. The methods used include education, training in making simple filters or filtration, and testing the results of water filtration from local sources in the disaster-affected area. The results of the activity show that the filter/filtration method using gravel, sand, activated charcoal, cotton, and palm fiber media can improve water quality visually and sensorily. This activity provides real benefits in supporting the availability of drinkable water for communities affected by the flash flood disaster, especially in the Aceh Tamiang area.